A study to assess the effectiveness of prone position on afterpains among postnatal women admitted in postnatal wards in Government Doon Medical College and Hospital Dehradun, Uttarakhand - Megha; Mohanta, Bijaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Afterpains are the irregular, spasmodic pains experienced in the lower abdomen between two and four days after delivery. The uterus contracts after delivery as it returns approximately to its pre-pregnancy size and position, resulting in these abdominal cramps. Methods: Quasi experimental, non-equivalent control group pre-test-post-test design was used to conduct the study at govt. Doon medical college and hospital, Dehradun. A total of 70 primi postnatal women were taken by using non-probability purposive sampling technique, following particular inclusion and exclusion criteria. The duration of the data collection was 4 weeks, from June 2023 to July 2023. Descriptive and inferential statistics was used to analyse the collected data. Results: The study revealed that the mean±SD of level of pain was 3.00±1.572 in experimental group and 4.89±1.183 in control group. The mean difference was 1.886 and calculated t=5.672 and p=.00001 hence the results is significant at p<0.001 level. Conclusions: It is concluded that after intervention there was significant difference between the pre-test level of afterpains and post-test level of afterpains in experimental group compared to control group.